STABILISASI DIMENSI PADA KAYU TANAMAN KARRI (Eucalyptus diversicolor) DAN JARRAH (E. marginata) - Bagian II : Furfurilasi (Dimensional Stabilization on Regrowth Karri (Eucalyptus diversicolor) and Jarrah (E. marginata) Part II : Furfurylation - Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Wood blocks of karri and jarrah measuring 10 mm (radial) x 25 mm (longitudinal) x 100 mm (tarigential) were ovendried for. 48 hours at 105°C prior to treatment. Furfurylation was carried out by soaking wood specimens in a 98. % furfuryl alcohol solution containing 1 % (w/w) of ZnCl2 as catalist. Three soaking times, i.e., 12, 24 and 48 hours were used. Treatment results are expressed in terms of weight (WG) and volumetric (VG) gains. The ability of treatment to dimensionally stabilize wood blocks is expressed as anti- swelling efficiency (ASE). Results showed that furfurylation imparted substantial increase in weight, volume and dimensional stability of both regrowth eucalypts. Alike acetylation (reported earlier in Part I),furfurylation on karri specimens revealed higher weight gain,volumetric gain and ASE than jarrah. The rate of furfurylation significantly increased with increasing soaking time to 48 hours. Although furfurylation imparted a high degree of swelling reductions comparable to those obtained by acetylation, the furfurylated specimens and a lower ability to resist swelling during prolonged wetting exposure.